Neoliberal Populism in Ontario: Premier Doug Ford’s Strategic Politics - Lucy Luccisano; Paula Maurutto (Norteamérica)
The 2018 election of Premier Doug Ford and the Progressive Conservative (PC) government ushered in a new era of neoliberal populism in Ontario, Canada. Ford’s election platform, titled a “Plan for the People,” resonated with the business elite who supported his free-market reforms but also with middle-class and blue-collar workers living in suburban and northern areas of the province. The article examines how Ford positioned his rivals as “out of touch” members of the political and cultural urban elite, responsible for a spiralling deficit that would economi-cally burden hard-working people. Unlike many other right-wing populist leaders, who have relied on xenophobic or anti-immigrant narratives, we argue that Ford’s populist stance is dema-gogic and pragmatic. This enabled him to pivot and shift his political strategy to amass support from a diverse range of economic, racial, ethnic, and religious groups, including new immigrants. We draw on newspaper articles, public documents and reports, as well as thirteen interviews with politicians, teachers and civil servants. The article highlights how Ford’s government operated to weaken democratic institutions through measures such as “strong mayor powers,” invoking the notwithstanding clause, as well as undermining the public sector. We trace how Ford’s populism undermined public education through overt and subtle measures that weaken school boards and unions while advancing privatization. We show how Ford bypassed intermediaries, in this case, school boards and teachers’ unions, and appealed directly to “the parents” through the media and employed cli-entelist strategies such as cash transfers under the guise of “parental choice” to hollow out public education. The analysis demonstrates how Ontario stands out as a unique case study for exam-ining neoliberal populism in Canada and North America.